2017
DOI: 10.1111/bph.13948
|View full text |Cite
|
Sign up to set email alerts
|

Pterostilbene reduces oxidative stress, prevents hypertrophy and preserves systolic function of right ventricle in cor pulmonale model

Abstract: The PTS : HPβCD complex prevented the maladaptative remodelling and protected systolic function in the RV of rats with pulmonary hypertension. These cardioprotective mechanisms may be related, in part, to the antioxidant potential of PTS, favoured by the increased p.o. bioavailability promoted by the presence of HPβCD in the complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 68 publications
4
26
1
Order By: Relevance
“…Our finding that increased enzymatic antioxidant activity in MCT‐injected rats is not sufficient to prevent oxidative stress leading to lipid peroxidation (Figure , Table ) suggests an altered capacity of the nonenzymatic antioxidant system. Our data showing unchanged thiol‐based nonenzymatic antioxidants in hypertrophied RV is in agreement with similar studies . However, a decline in nonenzymatic antioxidants in the heart was reported in the MCT‐induced RV hypertrophy model .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our finding that increased enzymatic antioxidant activity in MCT‐injected rats is not sufficient to prevent oxidative stress leading to lipid peroxidation (Figure , Table ) suggests an altered capacity of the nonenzymatic antioxidant system. Our data showing unchanged thiol‐based nonenzymatic antioxidants in hypertrophied RV is in agreement with similar studies . However, a decline in nonenzymatic antioxidants in the heart was reported in the MCT‐induced RV hypertrophy model .…”
Section: Discussionsupporting
confidence: 93%
“…Similar to other antioxidants B2BrBC and C66 treatment did not prevent RV hypertrophy (Table ) and this might be related to a weak effect of the applied dosages on pulmonary arterial function . Increased ROS are associated with proinflammatory and profibrotic events in the pressure‐overloaded myocardium and also induce antioxidant enzymes by direct activation of transcription factors .…”
Section: Discussionmentioning
confidence: 79%
“…Pterostilbene reduced malondialdehyde (MDA), 4‐hydroxynonenal (4‐HNE), aconitase‐2 and 8‐hydroxydeoxyguanosine (8‐OHdG) level; this suggests protective effects of pterostilbene on hyperosmolarity‐induced oxidative stress in human cornea epithelial cells . In vivo , Dos Santos Lacerda et al found that decrease in NADPH oxidase‐dependent superoxide anion production and oxidative stress may be the underlying mechanic of pterostilbene in cardioprotection, including maladaptative remodeling prevention and protection of systolic function in the right ventricle of rats with pulmonary hypertension . Pterostilbene also exerts protective activity on UVB‐induced skin damage and carcinogenesis by maintaining skin antioxidant defenses, including GSH levels, catalase, superoxide, and GSH peroxidase activities .…”
Section: The Effect Of Pterostilbene On Aging Biomarkersmentioning
confidence: 99%
“…Moreover, previous results suggest that the PTS ? HPbCD complex is as effective as noncomplexed PTS in terms of its antioxidant activity, thus indicating that the combination with HPbCD does not change this property (Dos Santos Lacerda et al 2017). Therefore, the decision was made to explore the classical enzymatic antioxidant system in both in vitro protocols.…”
Section: Discussionmentioning
confidence: 99%
“…All reagents were of analytical or HPLC grade. The complex was prepared using 0.3 M HPbCD dissolved in water with an excess of PTS (Dos Santos Lacerda et al 2017;Yeo et al 2013). The complex was solubilised in Dulbecco's modified Eagle's medium (DMEM) and tested at concentrations of 50, 100 and 150 lM to establish the optimal concentration for the pretreatment of cardiac myoblasts (experiment I).…”
Section: Preparation Of Pts ? Hpbcdmentioning
confidence: 99%